O treinamento de pais como instrumento de diminuição da violência - Sandra das Dores Souza (2013)
Violence is a problem that affects all individuals in a manner directly or indirectly, often appearing in the media and scientific statistics as a problem of today and should be seen in a multidisciplinary manner, since it features multiple causal factors should not be treated only as responsibilities of the authorities responsible for public safety, but as an issue that needs to be addressed by the whole society. We aimed to study the use of Training Parents can contribute to the prevention of violence, assuming that there is a relationship between stereotyped behavior and reproduction of violence.